A Brief Report on an 8-Week Course of Mindfulness-based Care for Chronic Pain in the Treatment of Veterans With Back Pain: Barriers Encountered to Treatment Engagement and Lessons Learned. Issue 9 (September 2020) - Eaton, Erica; Swearingen, Hannah R.; Zand Vakili, Amin; Jones, Stephanie R.; Greenberg, Benjamin D.
Abstract : Background: Chronic pain and associated symptoms are debilitating for veterans. Medical costs of treatments are high and current treatment options, most notably with opioid medications, have been associated with significant risk. Mindfulness-based interventions appear promising for chronic pain, but require additional testing in veteran care settings. Objective: This project was designed to test the feasibility of engaging and retaining veterans with chronic lower back pain in a new mindfulness protocol tailored for veterans, mindfulness-based care for chronic pain (MBCP). Clinical outcomes were also assessed. Design: An open pilot trial of an 8-week MBCP course that included meditation, gentle yoga, and psychoeducation. Subjects: Twenty-two veterans (mean age=49.77; 18% women) were recruited from a VA Medical Center in the Northeastern US. After screening for inclusion/exclusion criteria, 20 were eligible at baseline. Measures: Veterans were assessed at baseline and postintervention for functional impairment, pain intensity and bothersomeness, depression, and mindfulness. Results: The average number of sessions completed was 5; only 4 (20%) attended all sessions. Eleven of the 20 participants (55%) attended 5 or more sessions and had complete preintervention and postintervention visits. Five of the 11 had a clinically meaningful decrease in pain intensity and in depressive symptoms, while 6 of 11 had a meaningful decrease in pain bothersomeness and functional impairment. Conclusions: It was challenging to enroll and retain participants in this study, even with our intervention designed for veterans. We discuss possible adaptations and refinements in MBCP for veterans with chronic pain to enhance feasibility and improve upon these interventions. Abstract : Supplemental Digital Content is available in the text.